Future prospects for developing the current fleet of the Iraqi Oil Tanker Company - Al-Jazaerie , Hussein; Al-Jawarin , Adnan (The Gulf Economist, 2024)
Abstract: The Iraqi Oil Tankers Company is the only national carrier for transporting petroleum products and crude oil in Iraq. It has owned a marine fleet of (26) tankers since its establishment in 1972. However, as a result of the circumstances of the Iraq-Iran war and the Iraq war against Kuwait in the eighties and nineties of the last century, respectively, it led to the loss of its entire fleet until the change of the government regime in 2003. After that, the company began to restore its activity by purchasing (4) small-sized tankers to transport petroleum products in 2007 and 2009. Then it was able to build two tankers in 2020 and received them at the end of 2023, to transport fuel oil and naphtha products from the ports of Umm Qasr and Khor Al-Zubair to floating tanks in Iraqi territorial waters (the outer anchor area). Despite this, its current fleet does not fully meet the activity of transporting petroleum products, as the quantities transported exceed the fleet’s capacity, so the Iraqi Oil Tankers Company resorts to renting tankers to cover this activity.